Local homomorphisms of modular Lie algebras of Cartan type (in Ukrainian) - L. P. Bedratyuk (Математичні Студії, 2011)
Let L(m) be one of the finite dimensional modular Lie algebras W_n(m), S_n(m), H_n(m) and let L be one of corresponding p-algebras W_n, S_n, H_n. We prove that there exists a nontrivial map from the algebra S(L)^L of symmetrical invariants into the algebra S(L(m))^L(m).